2020
DOI: 10.3389/fneur.2020.597955
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Direct Current Stimulation to Enhance Cognitive Impairment in Parkinson's Disease: A Systematic Review and Meta-Analysis

Abstract: Cognitive deficits are increasingly being recognized as a common trait in Parkinson's disease (PD). Recently, transcranial direct current stimulation (tDCS) has been shown to exert positive effects as an adjunctive therapy on motor and non-motor symptoms in PD. This systematic review and meta-analysis aims to provide an overview of reported evidence on the efficacy of tDCS interventions in the treatment of cognitive impairments in PD. A systematic literature review was conducted to examine articles that were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Transcranial direct current stimulation is thought to modulate cortical excitability in regions such as the dorsolateral prefrontal cortex, influenced by but not necessarily dependent on cholinergic frontoparietal neural network dysfunction (97). A recent systematic review and metaanalysis suggested positive (though overall modest) effects of transcranial direct current stimulation on executive cognitive functions but highlighted the need for further research due to the lack of clear cause-effect relationship between the intervention and enhanced cognition (98).…”
Section: Non-invasive Neurostimulation Approachesmentioning
confidence: 99%
“…Transcranial direct current stimulation is thought to modulate cortical excitability in regions such as the dorsolateral prefrontal cortex, influenced by but not necessarily dependent on cholinergic frontoparietal neural network dysfunction (97). A recent systematic review and metaanalysis suggested positive (though overall modest) effects of transcranial direct current stimulation on executive cognitive functions but highlighted the need for further research due to the lack of clear cause-effect relationship between the intervention and enhanced cognition (98).…”
Section: Non-invasive Neurostimulation Approachesmentioning
confidence: 99%
“…These findings suggest a potential reason for the greater efficacy of temporal tDCS in individuals with AD compared to healthy controls. It appears that stimulating the DLPFC using tDCS is the most effective method for modulating cognitive functions, including memory, in healthy older adults ( Indahlastari et al, 2021 ) and in patients with Parkinson's disease ( Suarez-García et al, 2020 ). Therefore, it appears that patients with AD experience more advantages from temporal tDCS, whereas healthy individuals or patients with other neurodegenerative disorders may find tDCS in different brain regions more advantageous.…”
Section: Discussionmentioning
confidence: 99%
“…In PD, applications of tDCS showed to be able to produce transient beneficial effects, both in the motor [ 86 ] as well in the non-motor domains, particularly on cognition [ 87 ].…”
Section: Transcranial Direct Current Stimulation As a Therapeutic Option For Fatiguementioning
confidence: 99%